Modified Closed Coronary Transfer is a Good Alternative to the Trap-Door Method During Arterial Switch Operation: a Retrospective Propensity-Matched Comparison - Dedemoğlu,Mehmet (2020)
Abstract Objective: To compare the early and long-term results of patients in whom was performed modified closed coronary transfer with the results of patients in whom was performed trap-door transfer techniques by utilizing propensity-matching analysis to provide optimal identical patient matching for the groups. Methods: From August 2015 to December 2017, 127 consecutive patients underwent arterial switch operation due to simple and complex transposition of the great arteries, with or without additional arch and complex coronary pattern, by a single surgical team included into the study. Of these, in 70 patients it was performed modified closed coronary transfer technique and in 57 patients it was performed trap-door style coronary transfer technique. The patients were divided into two groups in terms of coronary transfer method. In the final model, after propensity matching, 47 patients from each group having similar propensity score were included into the study. Results: There was no significant difference between the groups regarding patient characteristics. Cross-clamp time and operation time were significantly lower in the modified technique group compared with the other group (P=0.03 and P=0.05, respectively). When compared the early and late postoperative outcomes, there was no significant difference between the groups. Postoperative echocardiographic findings were mostly similar between the groups. Conclusion: The patients in whom was performed our modified technique demonstrate overall good outcomes and the current technique ensures shorter arterial cross-clamp and operation times. It may be an alternative method to the trap-door technique for the coronary transfer during the arterial switch operation.